The modulating impact of cigarette smoking on brain structure in panic disorder: a voxel-based morphometry study. Issue 8 (30th July 2020) - Kunas, Stefanie L; Hilbert, Kevin; Yang, Yunbo; Richter, Jan; Hamm, Alfons; Wittmann, André; Ströhle, Andreas; Pfleiderer, Bettina; Herrmann, Martin J; Lang, Thomas; Lotze, Martin; Deckert, Jürgen; et al.
Abstract: Cigarette smoking increases the likelihood of developing anxiety disorders, among them panic disorder (PD). While brain structures altered by smoking partly overlap with morphological changes identified in PD, the modulating impact of smoking as a potential confounder on structural alterations in PD has not yet been addressed. In total, 143 PD patients (71 smokers) and 178 healthy controls (62 smokers) participated in a multicenter magnetic resonance imaging (MRI) study. T1-weighted images were used to examine brain structural alterations using voxel-based morphometry in a priori defined regions of the defensive system network. PD was associated with gray matter volume reductions in the amygdala and hippocampus. This difference was driven by non-smokers and absent in smoking subjects. Bilateral amygdala volumes were reduced with increasing health burden (neither PD nor smoking > either PD or smoking > both PD and smoking). As smoking can narrow or diminish commonly observed structural abnormalities in PD, the effect of smoking should be considered in MRI studies focusing on patients with pathological forms of fear and anxiety. Future studies are needed to determine if smoking may increase the risk for subsequent psychopathology via brain functional or structural alterations.